Women Writers in Review - Amanda Gagel (RIDE, 2017)
Women Writers in Review is the latest text corpus and digital humanities website to be produced by the Women Writers Project at Northeastern University. It includes over 600 reviews of women’s writing published between 1770 and 1830. The texts are encoded in TEI/XML and the site is easily navigable. It is a significant addition to the scholarship of early women’s writing, but would be greatly enhanced with further explanation on the site about its architecture and policies of transcription and tagging.